CRITERIA AND LEVELS OF ACTIVATION OF COGNITIVE ACTIVITY OF STUDENTS - Katerusha, O.V. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with criteria and levels of students’ activitation in terme of cognitivactivity.